Domains of Excellence: A CDC Framework for Developing High-Quality, Impact-Driven Public Health Science Publications - Parker, Erin M; Zhu, Bao-Ping; Li, Zheng; Puddy, Richard W; Kelly, Megan A; Scott, Colleen; Penman-Aguilar, Ana; Mekonnen, Mahider A; Stephens, James W (Journal of public health management and practice, 2024)
The Centers for Disease Control and Prevention (CDC) has a long history of using high-quality science to drive public health action that has improved the health, safety, and well-being of people in the United States and globally. To ensure scientific quality, manuscripts authored by CDC staff are required to undergo an internal review and approval process known as clearance. During 2022, CDC launched a scientific clearance transformation initiative to improve the efficiency of the clearance process while ensuring scientific quality. As part of the scientific clearance transformation initiative, a group of senior scientists across CDC developed a framework called the Domains of Excellence for High-Quality Publications (DOE framework). The framework includes 7 areas ("domains") that authors can consider for developing high-quality and impactful scientific manuscripts: Clarity, Scientific Rigor, Public Health Relevance, Policy Content, Ethical Standards, Collaboration, and Health Equity. Each domain includes multiple quality elements, highlighting specific key considerations within. CDC scientists are expected to use the DOE framework when conceptualizing, developing, revising, and reviewing scientific products to support collaboration and to ensure the quality and impact of their scientific manuscripts. The DOE framework sets expectations for a consistent standard for scientific manuscripts across CDC and promotes collaboration among authors, partners, and other subject matter experts. Many aspects have broad applicability to the public health field at large and might be relevant for others developing high-quality manuscripts in public health science. The framework can serve as a useful reference document for CDC authors and others in the public health community as they prepare scientific manuscripts for publication and dissemination.